Pengenalan Media Sosial Untuk Menciptakan Peluang Ekonomi di Karang Taruna Desa Panyirapan, Serang - Shanti Darmastuti; Mansur Juned; Syarif Ali; Jati Satrio (Indonesian Journal of Society Engagement, 2021)
The use of social media is increasing in society. This increase is motivated by the need for social interaction and other activities that require effective and fast paced delivery. Social media is also used to support business needs in integrated marketing. The economic benefits of social media are important to understand so that people can optimally use social media to create economic opportunities. Other than the positive impact, social media can also have negative impacts. In this regard, social media has become an interesting topic in community service activities at the Youth Organizations in Panyirapan Village, Serang Regency. Although Karang Taruna members have used social media a lot, they still have not understood the positive and negative impacts of social media in detail. Therefore, introducing social media to this community is important to provide an understanding of the positive and negative impacts of social media and the economic opportunities of social media. This includes initial coordination, the formation of a Whatsapp group to facilitate communication between the team and participants, pretest, counseling, and observation. The community were taught about the definition, form, impact, and economic opportunities of social media. The outreach activities ran smoothly, and the participants were interested in the business opportunities that could be obtained from the use of social media. The participants were also interested in knowing more about strategies in using social media to create further economic opportunities. From the results of the activity, our team thinks that public understanding regarding the use and utilization of social media is still at the basic stage.